Screw-Bone Implant Loosening: Complication, Cause and Assessment - A Ghani, M.; K. Ali Hassan, M.; Daud, R. (International Journal of Engineering and Technology, 2018)
Bone fracture has become more common in this era of vehicular modernization. Internal fixation has been used in the treatment of such cases. The use of screw and plate in internal fixation has been proven to provide more stability to fracture to promote better healing. The use of screw also carries certain risk such as self-loosening that can cause non-union and prolong healing. The complication of self-loosening is studied to comprehend the danger of self-loosening in screw-bone implant. The review on self-loosening in bolted joint is done in this paper to gain better understanding on the nature of self-loosening phenomena. The factor that affects the screw self-loosening in bone is further studied in the screw-bone implant environment. The identification of the screw loosening can be done with radiography, CT scan, MRI and ultrasound. This article have done a brief review on the complication of screw self-loosening, the cause of screw loosening in bolted joint and screw-bone implant and the assessment of screw loosening done by ultrasound and radiography.Â